Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Solve. 3d - 3 (d - 6) = 2 (d + 9)
A: 3d - 3 (d - 6) = 2 (d + 9) 3d - 3d + 18 = 2d + 18 18 = 2d + 18 -2d = 18 - 18 -2d = 0 d = 0
Question
Asked 9/3/2010 5:38:34 PM
Updated 2/25/2014 12:55:23 PM
1 Answer/Comment
Get an answer
New answers
Rating
3
3d - 3 (d - 6) = 2 (d + 9)

3d - 3d + 18 = 2d + 18

18 = 2d + 18

-2d = 18 - 18

-2d = 0

d = 0
Added 2/25/2014 12:55:23 PM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
What is a fused sentence
Question
Expert Answered
Updated 1/4/2015 8:41:34 AM
1 Answer/Comment
A fused sentence, also called a run-on, occurs when a writer has connected two main clauses with no punctuation.
Added 1/4/2015 8:40:41 AM
This answer has been confirmed as correct and helpful.
Confirmed by selymi [1/4/2015 8:41:36 AM]
Solve: 4 - 9x = 29 - 4x
Weegy: I'm sorry, i'm not good in math. (More)
Question
Expert Answered
Updated 2/26/2014 7:58:11 PM
1 Answer/Comment
4 - 9x = 29 - 4x

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5
Added 2/26/2014 7:58:11 PM
This answer has been confirmed as correct and helpful.
Solve for x: 4 - 9x = 29 - 4x
Weegy: 4 - 9x = 29 - 4x, -9x + 4x = 29 - 4, -5x = 25, x = 25/-5, x = -5 User: Solve for x: 13 + 5x = 22 + 8x Weegy: 13 + 5x = 22 + 8x, 5x - 8x = 22 - 13, -3x = 9, x = 9/-3, x = -3 (More)
Question
Expert Answered
Updated 2/26/2014 8:00:08 PM
0 Answers/Comments
Solve. 5x + 5 (x - 3) = 15
Weegy: x=3 (which would make it 15 + 0 = 15) (More)
Question
Expert Answered
Updated 191 days ago|12/9/2017 5:04:01 AM
1 Answer/Comment
5x + 5 (x - 3) = 15 ;

5x + 5x - 15 = 15 ;

10x = 15 + 15 = 30 ;

x = 30/10 = 3

Added 192 days ago|12/8/2017 2:41:44 PM
This answer has been confirmed as correct and helpful.
Confirmed by Masamune [12/9/2017 5:04:05 AM]
Solve. 10 - 5 (x - 5) = 4 (x - 1)
Weegy: x= 39/9 (More)
Question
Expert Answered
Updated 6/17/2014 5:31:04 AM
1 Answer/Comment
10 - 5 (x - 5) = 4 (x - 1)

10 - 5x + 25 = 4x - 4

-5x -4x = -4 - 10 - 25

-9x = -39

x = -39/-9

x = 13/3
Added 6/17/2014 5:31:04 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [6/17/2014 6:50:53 AM]
26,994,991 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 230 [Total 248] Ratings 0 Comments 160 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 105 [Total 256] Ratings 1 Comments 5 Invitations 9 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 60 [Total 13327] Ratings 0 Comments 60 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.